A comparison of endogenous and exogenous RNA reference marker as relevant for accurate Post-Mortem Interval estimation. Issue 1 (December 2019) - Uerlings, Sonja; Madea, Burkhard; Grabmüller, Melanie
Abstract: The Post Mortem-Interval (PMI), also known as time since death, is of relevance for forensic routine casework and serves primarily as the basis for the determination of the time that has passed since the time of death. The existing, "classical" approaches are characterised by certain limitations because they are predominantly based on morphological examinations. The present study deals with the assessment of two molecular messengerRNA-markers in different kinds post-mortem human specimens concerning their ability to use them for the estimation of the time of death. Moreover, a comparison between carefully selected endogenous and one exogenous reference marker for the normalisation of the gene expression data as relevant for accurate PMI estimation is drawn. The evaluation showed that the used approach is methodologically useful but on consideration of the achieved results it was only possible to determine slightly meaningful tendencies. The tested exogenous reference marker was not suitable for sufficient data normalisation whereas the endogenous reference markers showed a stable expression. However, it was not possible to recognise a specific expression level of the genes within a PMI group when endogenous reference markers were used.